Subclinical alexithymia modulates early audio-visual perceptive and attentional event-related potentials - Delle-Vigne, Dyna; Kornreich, Charles; Verbanck, Paul; Campanella, Salvatore (Frontiers in Human Neuroscience, 2014)
Introduction:Previous studies have highlighted the advantage of audio–visual oddball tasks (instead of unimodal ones) in order to electrophysiologically index subclinical behavioral differences. Since alexithymia is highly prevalent in the general population, we investigated whether the use of various bimodal tasks could elicit emotional effects in low- versus high-alexithymic scorers. Methods:Fifty students (33 females) were split into groups based on low and high scores on the Toronto Alexithymia Scale. During event-related potential recordings, they were exposed to three kinds of audio–visual oddball tasks: neutral (geometrical forms and bips), animal (dog and cock with their respective shouts), or emotional (faces and voices) stimuli. In each condition, participants were asked to quickly detect deviant events occurring amongst a train of frequent matching stimuli (e.g., push a button when a sad face–voice pair appeared amongst a train of neutral face–voice pairs). P100, N100, and P300 components were analyzed: P100 refers to visual perceptive processing, N100 to auditory ones, and the P300 relates to response-related stages. Results:High-alexithymic scorers presented a particular pattern of results when processing the emotional stimulations, reflected in early ERP components by increased P100 and N100 amplitudes in the emotional oddball tasks (P100: p< ,001; N100: p =,001)) as compared to the animal or neutral ones. Indeed, regarding the P100, subjects exhibited a higher amplitude in the AVE condition (8.7 µV), which was significantly different from that observed during the AVN condition (4.3 µV, p < 0.001). For the N100, the highest amplitude was found in the AVE condition (–4.0 µV) and the lowest was observed in the AVN condition (–2.6 µV, p = 0.003). However, no effect was found on the later P300 component. Conclusions:Our findings suggest that high-alexithymic scorers require heightened early attentional resources when confronted with emotional stimuli.